Development of a visual, patient-reported tool for assessing the multi-dimensional burden of endometriosis. (3rd August 2021) - As-Sanie, Sawsan; Laufer, Marc R.; Missmer, Stacey A.; Murji, Ally; Vincent, Katy; Eichner, Samantha; Cross, Sarah; Soliman, Ahmed M.; Tu, Frank
Abstract: Objective: Inadequate communication about endometriosis symptom burden between women and healthcare providers is a barrier for optimal treatment. This study describes the development of the EndoWheel, a patient-reported assessment tool that visualizes the multi-dimensional burden of endometriosis to facilitate patient–provider communication. Methods: Assessment questions for the tool were developed using an iterative Delphi consensus process. A consensus phase included additional practitioners and specialists to broaden perspectives and select revised statements. Semi-structured qualitative interviews were conducted with 13 women with endometriosis to assess the scoring and content of the measures. Results: Symptoms included in the tool were pelvic pain, vaginal bleeding, bowel/bladder symptoms, energy levels, fertility, impact on activities, emotional and sexual well-being, and self-perceived global health. Additional life impact areas included relationships, social and occupational activity, and self-perception. The 13 interviewees completed the tool in approximately 5–6 min (range 4.0–7.5 min). Most participants (92%) perceived that the tool would enable better patient–provider communication, including addressing symptoms and areas of impact not normally discussed during office visits. Conclusion: Similar to visual circular tools used in burden assessment of other chronic diseases, the tool may facilitate improved patient dialogue with providers around endometriosis treatment goals and options.